Analysis of Employee Engagement in PT kartina Trisatria - Fazary, Mario Herman; Gustomo, Aurik (Journal of Business and Management, 2016)
Abstract. PT. Kartina Trisatria is a nationwide company centered in Tanah Abang (the head office recently moved to Tanah Kusir, Jakarta) that has 83 direct employees and also has business partners (for production) with more than 1000 employees and also had implemented the employee engagement strategy, which is a concept that became very important human resource management strategy in companies worldwide, for their daily business activity. But even with the implementation of employee engagement, the employee turnover of PT Kartina Trisatria is still quiet high averaging 11.735% in 2009-2013 (PT. Kartina Trisatria, 2014). The purpose of this research is to find out which factor that affect the employee engagement in PT Kartina Trisatria and in the end will analyze about factors that need more improvements, in order to maintain the employee engagement within employees in the company. The employee engagement model this research will use is based on the American Society for Training and Development (ASTD) because it is suitable with the internal condition of the company to identify which driver variables of employee engagement needed to be improved. This research primary data was taken from questionnaire and interview with the employees in PT Kartina Trisatria. Then the questionnaire data was analyzed using the frequency test method with SPSS software. The interview was explained using narrative in the project. The analysis of the data showed this research that the driver variable that has the lowest score was the hygiene factor, which consists of resources and job salary given by the company. These researches gave suggestions about the improvement of the compensation system and also add some variables, which is position allowance, vehicle allowance, merit pay, and family allowance.Â Keywords: employee engagement, PT Kartina Trisatria, ASTD, compensation, Herzberg